A photoluminescence study of CuInSe2 single crystals ion implanted with 5 keV hydrogen. (8th February 2016) - Yakushev, M V; Krustok, J; Grossberg, M; Volkov, V A; Mudryi, A V; Martin, R W
Abstract: CuInSe2 single crystals ion implanted with 5 keV hydrogen at doses from 3  ×  10 14 to 10 16 cm −2 are studied by photoluminescence (PL). The PL spectra before and after implantation reveal two bands, a main dominant band centred at 0.96 eV and a lower intensity band centred at 0.93 eV. Detailed analysis of the shape of these bands, their temperature and excitation intensity dependencies allow the recombination mechanisms to be identified as band-to-tail (BT) and band-to-impurity (BI), respectively. The implantation causes gradual red shifts of the bands increasing linearly with the dose. The average depth of potential fluctuations is also estimated to increase with the dose and saturates for doses above 10 15 cm −2 . A model is proposed which associates the potential fluctuations with the antisite defects copper on indium site and indium on copper site. The saturation is explained by full randomization of copper and indium atoms on the cation sub-lattice.